DEIXIS IN THE LEGEND OF TANGKUBAN PARAHU STORY - Dina Indriani; Iman Santoso (PROJECT (Professional Journal of English Education), 2021)
Language it was really important in human life. Pragmatics is the ability of person to derive meanings from context of speech situation. This study is an attempt to analyzes a types of deixis are used in “The Legend of Tangkuban Parahu Story”. This study was purposed to find out of person deixis, place deixis, temporal deixis and identify which the most dominant of deixis that used in the story. This study only focused on the story. This story got from the Internet. The researcher choose to analyze the story because in the story there must be a contextual meaning. The researcher used descriptive qualitative method in this research. The steps to analyze data are searching the story, reading the story, and finding the data based on three types of deixis. The results of this research it can be concluded types of deixis that used in this story were person deixis, spatial deixis, and temporal deixis. In this research, there was 39 deixis found in the text. The most common type of deixis is person deixis which consist with 19 words. In this study, the researcher find out that person deixis is the most dominant type that found in the text. Keywords: Pragmatics, Deixis, Story